Whole Genome Sequences of the Raspberry and Strawberry Pathogens Phytophthora rubi and P. fragariae - Javier F. Tabima; Brent A. Kronmiller; Caroline M. Press; Brett M. Tyler; Inga A. Zasada; Niklaus J. Grünwald (Molecular Plant-Microbe Interactions, 2017)
Phytophthora rubi and P. fragariae are two closely related oomycete plant pathogens that exhibit strong morphological and physiological similarities but are specialized to infect different hosts of economic importance, namely, raspberry and strawberry. Here, we report the draft genome sequences of these two Phytophthora species as a first step toward understanding the genomic processes underlying plant host adaptation in these pathogens.